1996
DOI: 10.1111/j.1600-0897.1996.tb00037.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal HLA Class II Alleles Predispose to Pregnancy Losses in Danish Women With Recurrent Spontaneous Abortions and Their Female Relatives

Abstract: Maternal HLA-DR allogenotypes DR1/Br and -DR3 or closely linked genes seem to predispose to pregnancy losses in RSA patients and their first degree relatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…[1] Further among the UK RSA patient population linkage disequilibrium between A2 and B12 has been reported. [2] Various studies on HLA DR and DP loci have shown associations with RSA in Italian,[10] Danish,[69] and Japanese[578] populations. Recently, HLA DRB1*1502 has been reported to be significantly associated in Japanese RSA patients.…”
Section: Discussionmentioning
confidence: 99%
“…[1] Further among the UK RSA patient population linkage disequilibrium between A2 and B12 has been reported. [2] Various studies on HLA DR and DP loci have shown associations with RSA in Italian,[10] Danish,[69] and Japanese[578] populations. Recently, HLA DRB1*1502 has been reported to be significantly associated in Japanese RSA patients.…”
Section: Discussionmentioning
confidence: 99%
“…One of these (B8) was also found to be associated with smaller family size. A second human leukocyte anitgen (DR3) was also more common in lefthanded persons and Yeo and Gangestad (1998) noted that there is some evidence (Christiansen et al, 1996) that this allele is associated with spontaneous abortions. It should be noted, however, that the association of left-handedness with the DR3 allele was based on only nine left-handed individuals.…”
Section: Introductionmentioning
confidence: 96%
“…In line with these hypotheses, Gangestad et al (1996) reported that a human leukocyte antigen (B8) was related to both left-handedness and to reduced offspring number in their study. They also found that left-handedness was related to the human leukocyte antigen DR3, and Yeo and Gangestad (1998) noted that this antigen has been found by Christiansen et al (1996) to be associated with an increased risk of spontaneous abortion in women. We assessed the first hypothesis through a study of the family sizes of 2083 families with two righthanded parents and 502 families having one or more left-handed parents; we assessed the second hypothesis from miscarriage history data supplied by 300 dextral and 52 sinistral mothers.…”
mentioning
confidence: 93%
“…Genes and polymorphism in the human leukocyte antigen (HLA) region on the short arm of chromosome 6 have been associated with reproductive success, with the development of preimplantation embryos and with certain complications during pregnancy [1][2][3][4][5][6][7][8][9]. In mice, litter size and birth weight have been associated with the expression of a Ped phenotype encoded by the Qa-2 gene in the MHC [10].…”
Section: Introductionmentioning
confidence: 99%